2021
DOI: 10.1093/eep/dvab014
|View full text |Cite
|
Sign up to set email alerts
|

Developmental exposure to methylmercury and ADHD, a literature review of epigenetic studies

Abstract: Attention-deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder that affects the competence of academic performance and social wellness in children and adults. The causes of ADHD are unclear. Both genetic and environmental factors contribute to the development of ADHD. The behavioral impairments in ADHD are associated with epigenetic changes in genes that are important for neurodevelopment. Among environmental causes of ADHD, the neurotoxin methylmercury (MeHg) is associated with an increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…The researchers’ hypothesis for this mechanism of action is that artificial food colorings can induce nutritional deficiencies, which could result in impaired neuronal development. Researchers such as Ke et al [ 37 ] associate it with the accumulation of heavy metals such as mercury in the bodies of these children due to the ability of synthetic dyes to modify the levels of zinc and manganese.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers’ hypothesis for this mechanism of action is that artificial food colorings can induce nutritional deficiencies, which could result in impaired neuronal development. Researchers such as Ke et al [ 37 ] associate it with the accumulation of heavy metals such as mercury in the bodies of these children due to the ability of synthetic dyes to modify the levels of zinc and manganese.…”
Section: Discussionmentioning
confidence: 99%
“…Dopaminergic neurotransmission is involved in cognitive processes such as the reward system, muscular control, and emotion regulation. The effectiveness of dopamine neurotransmission stimulants in treating ADHD shows that the normal dopaminergic neurotransmission in ADHD patients may have been interrupted [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…This effect may be further increased by zinc deficiency, which is associated with a loss in blood-brain barrier integrity in zinc-deficient mice [ 20 ]. Since studies have shown that heavy metals like mercury may cause susceptibility to ADHD in children due to its effect on neurodevelopment [ 21 ], the zinc deficiency that AFCs can cause could be a factor in ADHD symptom exacerbation. This is further supported by studies that have shown that treating patients with ADHD with zinc sulfate decreased hyperactive and impulsive symptoms in those patients [ 22 ].…”
Section: Reviewmentioning
confidence: 99%